ИСПОЛЬЗОВАНИЕ МАНУАЛЬНОЙ ТЕРАПИИ В ЛЕЧЕНИИ ПЕРВИЧНОГО НОЧНОГО ЭНУРЕЗА (World Science, 2019)
Primary nocturnal enuresis is a fairly common disease among children over five years old and while it tends to go away in most of them over time without any treatment, for many, bedwetting continues to be an emotionally stressful and socially destructive state of the early years of their childhood. The presence of a vertebrogenic factor in the clinical picture of primary nocturnal enuresis justifies the use of manual therapy in treating this disease and if the said vertebrogenic factor proves to be the determining cause of the disease, manual correction will allow to quickly, non-invasively, economically, effectively, safely, side-effectlessly and completely eradicate the disease even in cases where treatment by other methods was unsuccessful.